Study about Student’s Perception toward the Use of Smart TV in Learning Speaking on the Material Giving and Asking of Instructions - Vindy Nita Yusovi; Muhtarom Muhtarom; Enok Purwanti (PANYONARA: Journal of English Education, 2023)
To improve students' ability to speak passively especially in teaching asking and giving instructions material, supporting devices are needed since students need media or teaching strategies that are relevant. The purpose of this study was to discuss more deeply in the context of students’ perception about the use of Smart TV on the learning process in the classroom which is also related to the problems experienced by students and also to the output produced by students. The design of the study was descriptive qualitative. The subjects of the study were 19 students from 34 students in MTsN Gresik at 8 th grade. The data was collected through a questionnaire, interview and the student’s own performance. The study revealed that students responded to Smart TV as a media in learning speaking on the material asking for and giving instructions are positive: they strongly agreed that by using Smart TV, the learning process more lively, fun and meaningful.